Biocatalytic conversion of lipids from microalgae Scenedesmus obliquus to biodiesel using Pseudomonas fluorescens lipase. (1st May 2015) - Guldhe, Abhishek; Singh, Bhaskar; Rawat, Ismail; Permaul, Kugen; Bux, Faizal
Highlights: Biocatalytic biodiesel conversion of microalgal lipids is greener and sustainable. Microalgal feedstock Scenedesmus obliquus was cultivated in an open circular pond. Immobilized P. fluorescens lipase showed better conversion among selected lipases. Immobilized P. fluorescens lipase can be reused for 4 repeated batches. Fuel properties of biodiesel showed compliance with the international standards. Abstract: Conversion of microalgal lipids using biocatalyst is a novel and greener approach to produce biodiesel. Free and immobilized lipases from Candida sp. and Pseudomonas fluorescens along with free lipases from porcine pancreas and wheat germ were screened for biodiesel conversion of Scenedesmus obliquus lipids. Among selected lipases from various sources immobilized lipase from P. fluorescens showed superior biodiesel conversion. Optimization of reaction parameters viz. lipase amount, temperature, methanol to oil molar ratio and water content was carried out using response surface methodology. Best conversion of 66.55% was achieved at 35 °C, methanol to oil ratio of 3:1 with 10% enzyme amount and 2.5% water content based on oil weight. To tackle methanol tolerance step-wise methanol addition was applied, which improved biodiesel conversion upto 90.81%. Immobilized P. fluorescens lipase can be used for 4 batches without much loss in conversion efficiency (>95%). Biodiesel produced has the cetane number of 51.77, Calorific value of 37.67 MJ kg −1 . Most of the fuel properties of biodiesel met the specifications set by ASTM and EN standards.